Le dernier des Aloukous de Roland Brival : un point de non retour - Yolande Aline Helm (Études Caribéennes)
The article examines the precarious existence of the Alukus, a population based in Guyana, and the descendants of maroons slaves. The study is based on a novel by Roland Brival, one of the few writers from the French Caribbean who has paid a tribute to this ethnic group threatened by modernization and urbanization. It also examines issues of deforestation, deterritorialization, and the importance of rituals and gods in the Alukus' culture.